PERLINDUNGAN KONSUMEN DAN PENERAPAN ASAS MASHLAHAH DALAM PRAKTEK JUAL BELI PAKAIAN BEKAS DI KOTA MATARAM - Nasrullah Nasrullah; Mega Trikayanti (Universitas Islam Negeri Mataram, 2023)
The rise of the practice of selling used clothing today as an alternative to fulfilling casual needs at a relatively low cost is quite attractive to various groups. On the other hand, the practice of selling used clothing often causes problems for consumers as a result of the absence of adequate information regarding the origin and quality of the goods sold, so that consumers get clothes that are basically unfit for use without prioritizing the principle of benefit (mashlahah). This research uses normative legal research methods, namely by examining existing legal norms in consumer protection laws and provisions of related legislation and their derivatives using a statutory approach, case approach, and conceptual approach. The results showed that the practice of selling used clothing was not carried out in accordance with the provisions of the applicable laws and regulations and tended to ignore consumer protection and could not guarantee the realization of benefits (mashlahah) in the sale and purchase practice.